Students’ viewpoints on strategic notetaking and its impact on mathematical performance, achievement, and learning / Muniroh Hamat ... [et al.] - Hamat, Muniroh; Mahlan, Siti Balqis; Shamsuddin, Maisurah; Mohamed, Siti Asmah (Unit Penerbitan JSKM, 2022)
Taking notes is a widely used pedagogical strategy in all fields of education. Taking strategic notes benefits students because it becomes part of the way so students can learn, and it can help students show better performance in the courses studied. In higher education, there has been a strong effort to engage students in collaborative notetaking to increase their engagement with the material and inspire deeper and more meaningful learning. Take notes are strategically seen as an essential skill needed in a university environment. It involves active listening, processing information and writing. Results from several studies indicate that strategic note - taking can improve higher performance and achievement. Taking the right notes is a skill that many deficiencies by students. However, it is unclear if notetaking has a significant impact on student achievement. The objective of this research study was to determine whether strategic notetaking can increase performance, achievement and learning in mathematics subjects.